2022
DOI: 10.1080/13557858.2022.2128069
|View full text |Cite
|
Sign up to set email alerts
|

First-generation Nigerian mothers living in the UK and their experience of postnatal depression: an interpretative phenomenological analysis

Abstract: Objective: Previous studies emphasise the negative psychological and physical consequences of Postnatal Depression (PND) on mothers and children's health.In the UK, around 10-20% of women can be affected by perinatal mental health problems. Minority ethnic groups such as Black African mothers are considered to be at greater risk of developing PND and data estimates that immigrant mothers are twice more likely to develop PND than native mothers. The unique experiences and needs of this culturally diverse group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 34 publications
(40 reference statements)
0
17
0
Order By: Relevance
“…In addition to conceptualization, four other dominant themes emerged on PND: (1) isolation–a lack of social, cultural support (i.e., lack of hands-on support for mother and child from immediate family and community), emotional support (i.e., having someone to talk to), and professional support (i.e., lack of on-going support from professional postpartum); (2) loss of identity, including loss of one’s old self and old life (mourning the loss of who they once were); (3) issues of trust—distrust in others due to fear of betrayal and fear of stigma (from community members); (4) relationships facilitate recovery–work and other activities are helpful distractors, better relationship with baby was helpful for recovery, maternal support services and groups help reduce distress and facilitate recovery. In a related study, Ling et al [ 41 ] assessed the lived experiences of Nigerian mothers in the UK who had experienced PND. Three main themes were identified, including seven sub-themes: (i) Socio-cultural factors (inter-generational expectation to conform to the strong Black woman identify; cultural perceptions of shame and stigma around PND made it difficult for women to open up; and transitions/adjusting to a new culture led to isolation and loss of community support); (ii) What about me?…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to conceptualization, four other dominant themes emerged on PND: (1) isolation–a lack of social, cultural support (i.e., lack of hands-on support for mother and child from immediate family and community), emotional support (i.e., having someone to talk to), and professional support (i.e., lack of on-going support from professional postpartum); (2) loss of identity, including loss of one’s old self and old life (mourning the loss of who they once were); (3) issues of trust—distrust in others due to fear of betrayal and fear of stigma (from community members); (4) relationships facilitate recovery–work and other activities are helpful distractors, better relationship with baby was helpful for recovery, maternal support services and groups help reduce distress and facilitate recovery. In a related study, Ling et al [ 41 ] assessed the lived experiences of Nigerian mothers in the UK who had experienced PND. Three main themes were identified, including seven sub-themes: (i) Socio-cultural factors (inter-generational expectation to conform to the strong Black woman identify; cultural perceptions of shame and stigma around PND made it difficult for women to open up; and transitions/adjusting to a new culture led to isolation and loss of community support); (ii) What about me?…”
Section: Resultsmentioning
confidence: 99%
“…Barriers were explored only in the studies, which investigated PND in migrant women of African origin [ 39 41 ]. Barriers identified included African cultural beliefs about mental health (e.g., bewitchment), cultural expectation to be a strong woman, cultural shame and stigma around mental health challenges, racial discrimination from health providers during maternal care, neglect from health visitors and midwives due to excessive focus on the child’s health and limited focus on the mother’s wellbeing, neglect from GPs, and GPs limited tendency to involve new mothers in treatment decisions, temporary immigration status (which often limits their accessibly to health care services), stress of navigating the health system [ 39 , 41 , 42 ], lack of support from partner, and lack of trust of others in community due to fear of stigma and profiling [ 40 , 41 ]. Facilitators of help-seeking behaviors reported in the other studies were proficiency in the English language ( p = 0.010) and a higher level of education ( p = 0.002)- in the USA migrant group [ 35 ]; sensitizing migrant women about maternal mental health and postpartum mental health services, reaching out to immigrant women, providing services that protest their confidentiality (e.g., online services) [ 39 ], and having access to health professionals that could provide a safe space for confidential conversations–in new-born mothers with PND [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First-generation Nigerian mothers living in the UK 45 encountered di culties with post-natal depression, including neglect from family and healthcare professionals, and self-reliance as a coping strategy. Contrary to reports suggesting that black ethnic groups do not seek help for their mental health needs 44 , mothers reported that their attempts to engage with professionals were met with unsatisfactory responses 45 . Black Caribbean women appeared invisible in mainstream mental health services and associated research.…”
Section: Access To Perinatal Services and Ethnicity In The Ukmentioning
confidence: 99%